A Conversation with Architects: Paul Oliver and the Anthropology of Shelter. Issue 1 (2nd January 2016) - Vellinga, Marcel
Abstract : Throughout a career that spanned nearly 45 years, Paul Oliver consistently put forward his ideas on why an anthropological approach to architecture would be beneficial to the understanding of the design, use, and meaning of buildings. This article intends to explore Oliver's views and writings on the relationship between architecture and anthropology. It aims to provide an overview of Oliver's oeuvre and approach, to position it in the context of other contemporaneous writings on architecture and anthropology, and to assess the influence of his work on later discourses. It will argue that, first and foremost, Oliver wrote for an architectural audience, rather than an anthropological one. Instead of wanting to engage in a direct dialogue about architecture with anthropologists, Oliver's main intention was to increase architects' awareness of the cultural embodiment of architecture. A better realisation of the intricate relation between architecture, society, and culture would lead not just to a better understanding of why architecture takes the form it does, but ultimately also to more culturally appropriate contemporary design. Oliver's main aim, then, was to make architects aware of the value and usefulness of anthropology, rather than to engage in a conversation with anthropology itself. The article concludes that Oliver's work remains as relevant to architectural discourse today as it ever was during the 45 years of his career.